2005
DOI: 10.1007/s10024-005-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Telangiectatic Focal Nodular Hyperplasia of the Liver in the Perinatal Period: Case Report

Abstract: We report a case of congenital telangiectatic focal nodular hyperplasia, a rare variant form of the disease. The patient was a 2-month-old boy whose parents noticed abdominal distention about 2 weeks after birth, and ultrasonogram revealed a large mass in the liver. He underwent right lobectomy, and gross findings showed an ill-defined mass without any central scar. Histologic findings demonstrated proliferating hepatocytes without atypia arranged in cords of 1- or 2-cell thickness with marked sinusoidal dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Yet this does not have to be the case, as even monoclonality is neither necessary nor sufficient to characterize a proliferation of cells as being neoplastic in the classical sense of the term. Chromosomal abnormalities have been reported in multinodular thyroid goiters [10] and focal nodular hyperplasia of the liver [11]. The high MIB-1 proliferative index, demonstrated in the epithelioid component of this lesion, is also compatible with the concept of nodular hyperplasia, having been demonstrated in thyroid hyperplastic lesions, nodular goiters, and Graves' disease [12].…”
Section: Discussionmentioning
confidence: 85%
“…Yet this does not have to be the case, as even monoclonality is neither necessary nor sufficient to characterize a proliferation of cells as being neoplastic in the classical sense of the term. Chromosomal abnormalities have been reported in multinodular thyroid goiters [10] and focal nodular hyperplasia of the liver [11]. The high MIB-1 proliferative index, demonstrated in the epithelioid component of this lesion, is also compatible with the concept of nodular hyperplasia, having been demonstrated in thyroid hyperplastic lesions, nodular goiters, and Graves' disease [12].…”
Section: Discussionmentioning
confidence: 85%
“…Whereas, vascular disorders and another hepatic lesions revealed by effect of raw vetch seed. It is reported that increased arterial flow leads to sinusoidal dilatations (Okamura et al, 2005). Irregular sinusoidal structures also give signs of congestions (Ozturk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…TFNH can present with clinical hemorrhage, abdominal pain, abnormal liver function tests (mainly increases in gamma glutamyltranspeptidase or alkaline phosphatase) or as an incidental discovery during the performance of a radiological procedure. In all previously reported pediatric cases, TFNH clinically presented with abdominal mass but without jaundice or cholestasis [7][8][9]. Also, there are some cases related to neoplasms, vascular malformations and liver diseases like primary biliary cirrhosis and chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 98%
“…In children, the scarce descriptions of TFNH report common features like the lack of FNH typical central scar at imaging and the presence of enlarged and proliferating vessels with strong expression of CD34 in the telangiectatic sinusoids at histopathologic examination [7][8][9]. Very little data is available about the pathogenesis of TFNH but the use of molecular techniques has shown that they are monoclonal lesions similar to HA although they do not carry HNF1α mutations [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation